Adaptation of ENDS Device Measurements into Puffing Topography Variables and Clinical Implications - Oldham Michael J.; Cook David K.; Liang Qiwei; Fraley Norman; Singletary Buddy; Anderson Samuel; Vinnakota Abhiraj; Gillman I. Gene (Contributions to Tobacco and Nicotine Research)
Some next generation electronic nicotine delivery systems (ENDS) are capable of providing measurements of selected device parameters related to classical puffing topography variables (e.g., number of puffs, puff duration, etc.) and estimated aerosol mass. The JUUL2® System can provide some of this information via a mobile phone application. A laboratory study was used to compare and translate selected device measurements into classical puffing topography variables for the breath activated JUUL2® device. The sensitivity of the pressure sensors that activate the device were determined using 7 flowrates in a pressure-flow testing apparatus using 30 JUUL2® devices. The JUUL2® device tracks activation duration as a proxy for puff duration. Comparison of puff duration from a puffing machine to device activation duration was performed using three different puffing regimens for 15 JUUL2® devices with a tobacco and menthol formulation. An ISO 20768 square wave, sine wave, and gap wave puffing regimens were used. The gap wave was created from the ISO 20768 square wave puffing regimen with a 0.5-s gap in the middle of the 3-s puff (gap puffing regimen with a 2.5-s puff duration), and all puff regimens were 3 seconds in duration. For each puffing regimen, the gravimetrically determined device mass loss and aerosol collected mass was compared to the estimate of generated aerosol mass provided by the JUUL2® device. Pressure-flow testing demonstrated that device activation occurred at a pressure drop of 95–150 Pa, which corresponded to a flowrate of 7.5–10 cm3/s. The duration of JUUL2® device’s activation averaged 95% and 76.4% of the 3-s puff duration of the square wave and sine wave regimens, respectively. For the gap wave regimen, the JUUL2® activation duration averaged 91% of the 2.5-s puffing regimen. There were small but statistically significant differences in device activation duration between the Virginia Tobacco and Menthol formulations using the square wave and gap wave puffing regimen. For a few puffs, the JUUL2® device recorded two activations, rather than one, with the incidence more pronounced for the sine wave than the square wave puffing regimen. A simple algorithm was developed that combined split device activations so that they perfectly matched puff counts during the square wave and sine wave puffing regimens. For each formulation (tobacco and menthol) and puffing regimen, there was a different correlation between the estimated aerosol mass from the JUUL2® device and the gravimetrically measured device mass loss. When puffing regimens were combined for each flavor, there was good correlation between measured device mass loss or aerosol collected mass and the estimated aerosol mass from the JUUL2® device. In conclusion, selected JUUL2® device measured parameters can be translated into classical puffing topography variables (i.e., number of puffs and puff duration), as well as provide an estimated aerosol mass generated by the JUUL2 System.